Stakeholders' knowledge of threatened freshwater fishes and their involvement in fishery value chains in order to assist conservation in developing countries - Galib, Shams M.; Naher, Sheratun; Arnob, Sadman S.; Khatun, Mst. Tasnima; Reza, Md. Selim; Parvez, Md. Taskin; Sun, Jingrui; Lucas, Martyn C. (Frontiers in Freshwater Science, 2023)
Introduction Improved conservation of exploited freshwater biodiversity is an increasing priority globally, but in developing countries there is often little insight of stakeholder attitudes within the value chains through which exploited species are passed, upon which to make informed management decisions. Methods We determined knowledge concerning threatened freshwater fishes in Bangladesh by key stakeholder groups (fishermen, faria agents, commission agents, retailers and consumers; n = 485 respondents) and their participation level in the threatened fish value chain. We also determined factors affecting local ecological knowledge and participation in the value chain. Results and discussion The highest mean number of threatened fish species (4.8 ± 3.5% of species) was identified by the fishermen group, whereas consumers identified fewest (0.5 ± 1.1% of species). All respondent groups participated in the threatened fish value chain and their participation varied across respondent groups. 45.3% of the total number of threatened fish species appeared in the value chain. Participation level was highest for commission agents, involved in the trade of 21.5 ± 4.2% of threatened fish species, and lowest for consumers (7.4 ± 6.5% of threatened species). For fishermen, the principal component “experience-income-age” and the interaction between education and financial loan factors affected fishers' participation in the threatened fish value chain positively whereas, this was negatively affected by their knowledge level of threatened fishes. This study reveals the poor knowledge of stakeholder groups regarding threatened fishes, but establishes their active participation in the value chain of these species in Bangladesh. With limited resources for conservation of threatened species in many developing countries, it is very risky to implement commonly used in-situ conservation methods (e.g., habitat quality improvement) without fuller buy-in from the stakeholders. Conclusions We recommend specific protection laws for threatened fishes and awareness building campaigns for stakeholder groups to ensure minimum impact to threatened fish species. As overharvesting is a major cause of threatened fish species decline, such training programmes should be designed for fishers in developing regions. Education programmes on threats to ecosystems and biodiversity should be prioritized in schools and fishing communities. In addition, regular monitoring for protected species at harvesting sites and fishing markets should be ensured.